A Step-by-Step Approach to Ensure Asset Performance Based on Technical Documentation. Issue 21 (2015) - Koukias, Andreas; Kiritsis, Dimitris
Abstract: The physical or engineering assets within modern industries have consistently been considered as the core elements of significant value that constitute the backbone for success and overall growth. The management of any asset within an industrial environment is heavily supported by the overall usage and maintenance instructions specifying a variety of information concerning the asset and dictating how the asset should be overall optimally managed. These instructions have traditionally been in the form of a textual and graphical technical documents compilation that is created by the manufacturer and exclusively intended for the asset user. However, the content of these documents may be poorly or partly consumed by the asset users thus creating a gap between the original documentation instructions and the actual asset usage. This paper describes a step-by-step approach to represent the knowledge included in the technical documentation. Ontologies are proposed because they possess high expressive power, degree of formality, and most importantly they are machine understandable. The approach proposes the implementation of a rule-based mechanism in order to identify divergences from the documentation towards taking appropriate corrective actions and eventually ensuring or even optimizing the asset performance.